Business analysis : best practices for success - Blais, Steven (Hoboken, N.J. : Wiley, 2012)
'The definitive guide on the roles and responsibilities of the business analystBusiness Analysis offers a complete description of the process of business analysis in solving business problems. Filled with tips, tricks, techniques, and guerilla tactics to help execute the process in the face of sometimes overwhelming political or social obstacles, this guide is also filled with real world stories from the author's more than thirty years of experience working as a business analyst. Provides techniques and tips to execute the at-times tricky job of business analyst Written by an industry expert with over thirty years of experience Straightforward and insightful, Business Analysis is a valuable contribution to your ability to be successful in this role in today's business environment'--
Includes index.
Keywords: Business analysts; Business planning; Organizational effectiveness; BUSINESS & ECONOMICS / Project Management